Pengembangan Media Flipbook dalam Membaca Permulaan Siswa Kelas II SDN 7 Suwawa Kabupaten Bone Bolango - Amelia Ishak; Rusmin Husain; Fidyawati Monoarfa; Wiwy Triyanty Pulukadang; Ade Mahniar (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aimed to develop a feasible and practical flipbook medium to support early reading skills among second-grade students at SDN 7 Suwawa, Bone Bolango Regency. Initial conditions showed that learning activities were still dominated by printed books, causing some students to experience difficulties in recognizing letters, reading syllables, and understanding simple words. This study employed a Research and Development method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The flipbook was organized into five reading levels under the theme “Let’s Live Healthy” and developed using Canva, CapCut, and Heyzine. Its feasibility was assessed by media, material, language, and user experts, while practicality was tested on 27 students. The results showed an average feasibility score of 92.10%, categorized as Highly Feasible, and a practicality score of 98.61%, categorized as Highly Practical. Therefore, the flipbook is feasible and practical for supporting early reading instruction in elementary schools.